Ethno-Racial Variation in Recovery From Severe Mental Illness: A Qualitative Comparison. (June 2016) - Whitley, Rob
Objective: Purpose-driven studies examining the relationship between ethnicity, culture, and recovery are absent from the empirical literature. As such, the overall aim of this study was to examine ethno-racial variations in recovery perspectives. Specific objectives consist of comparing and contrasting ethno-racial variations in 1) definitions of recovery, 2) barriers to recovery, and 3) facilitators of recovery. Methods: We recruited people with severe mental illness from 2 broad ethno-racial groups (Caribbean-Canadian and Euro-Canadian) to partake in a qualitative interview on recovery ( n = 47). Participants were asked to give their own definitions of recovery, as well as self-perceived barriers and facilitators. Interview transcripts were then subjected to thematic analysis. We compared and contrasted the distribution and salience of emerging themes between the Euro-Canadian and Caribbean-Canadian participants. Results: Recovery was consistently defined as a gradual process involving progress in key life domains including employment, social engagement, and community participation by both groups. This was underpinned by a growing future orientation. Stigma, financial strain, and psychiatric hospitalization were considered major barriers to recovery in both groups. Participants from both groups generally considered stated definitions of recovery to be simultaneous facilitators of recovery—employment and social engagement being the most frequently mentioned. God and religion were key facilitators for the Caribbean-Canadian group but not for Euro-Canadians. Conclusions: Definitions, barriers, and facilitators to recovery were generally shared among our sample, regardless of ethno-racial status, with the exception of God and religion.